A Bit of Ripping and Tearing: An Interpretative Study of Indigenous Engagement Officers’ Perceptions Regarding Their Community and Workplace Roles - Mason, John; Southcott, Jane (The Australian Journal of Indigenous Education, 2019)
The Australian Government (AG) employs Indigenous Engagement Officers (IEO) in many of the remote Aboriginal communities of the Northern Territory (NT). IEOs are respected community members who apply their deep understanding of local tradition, language and politics in providing expert cultural advice to government. Competing priorities of workplace and cultural obligation make the IEO role stressful and dichotomous in nature. The workplace experiences and perceptions of IEOs remain largely unexplored and there is scant understanding of the significant crosscultural issues associated with the role. IEOs typically confront ongoing workplace stress and are unable to perform at full capacity. This qualitative study explores participant meaning regarding workplace and community roles to inform the AG in development of culturally appropriate training and support for IEOs. The study captures detailed information from six IEOs through an interpretive process sensitive to phenomenological experience. Personal meanings associated with the workplace are assembled through individual interviews and focus group sessions. Interpretative Phenomenological Analysis methodology is applied to the resulting idiographic dataset in exposing a range of superordinate themes including desire for recognition and feelings of abandonment. Findings reveal the need to incorporate correct cultural protocols in the workplace and give preference for Aboriginal learning styles in professional development activities. There is urgent need for a range of workplace supports for IEOs in future capacity-building strategies.